Biomarkers of GH deficiency identified in untreated and GH-treated Pit-1 mutant mice - Al-Samerria, Sarmed; Xu, Huiting; Diaz-Rubio, M. Elena; Phelan, Joseph; Su, Chi; Ma, Keer; Newen, Anna; Li, Kiana; Yamada, Sayaka; Negron, Ariel L.; Wondisford, Fredric; Radovick, Sally (Frontiers in Endocrinology, 2025)
BackgroundGrowth Hormone Deficiency (GHD) is marked by insufficient growth hormone (GH) production, leading to disruptions in growth and metabolism. Its diagnosis is challenging due to the lack of sensitive, specific tests. To address this, we used a novel mouse model with a POU1F1 (Pit-1) gene mutation (K216E). This study aimed to identify metabolic biomarkers of GHD and assess their responsiveness to GH therapy, alongside pathway analysis to uncover disrupted metabolic pathways.MethodsThe Pit-1^K216E mouse model was validated for GHD through assessments of GH production, growth, and body composition. Metabolomic profiling was conducted to identify biomarkers, while pathway analysis examined disrupted metabolic pathways and their response to GH treatment. This approach aimed to improve understanding of GHD’s metabolic impact and potential therapeutic strategies.ResultsThe assessment of the Pit-1^K216E mouse confirmed GHD, as evidenced by reduced GH production and altered body composition. Metabolomic profiling identified three distinct biomarker groups associated with GHD: (1) GHD Biomarkers, found exclusively in GH-deficient mutant mice but absent in WT controls; (2) GH Treatment Responsive Biomarkers, which were altered in GH-deficient mutant mice (GHD) and further modulated following GH treatment, reflecting a response specific to the GHD condition and its treatment, but not observed in WT mice; and (3) GH Treatment-Specific Responsive Biomarkers, observed exclusively in the GHD condition after GH therapy. Pathway analysis revealed significant disruptions in purine metabolism, amino acid metabolism, and protein synthesis, with notable sex-specific differences. Male mice exhibited imbalances in taurine and hypotaurine metabolism, while female mice showed disruptions in tyrosine metabolism and mitochondrial function, highlighting sex-dependent metabolic responses to GHD and GH therapy.ConclusionThe Pit-1^K216E mouse model offers a robust platform for exploring GHD’s molecular mechanisms. The identification of distinct, sex-specific metabolic biomarkers provides insights into GHD-related metabolic disruptions and supports personalized management strategies. These findings establish a framework for leveraging metabolic biomarkers to enhance the diagnosis and monitoring of GHD, with promising applications for future human studies and therapeutic strategies.